2023
DOI: 10.3390/antibiotics12040657
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Prevalence and Antimicrobial Resistance of Enterococcus faecalis and Enterococcus faecium Associated with Poultry in Four Districts in Zambia

Abstract: The presence of antimicrobial-resistant Enterococci in poultry is a growing public health concern worldwide due to its potential for transmission to humans. The aim of this study was to determine the prevalence and patterns of antimicrobial resistance and to detect drug-resistant genes in Enterococcus faecalis and E. faecium in poultry from four districts in Zambia. Identification of Enterococci was conducted using phenotypic methods. Antimicrobial resistance was determined using the disc diffusion method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“… 9 , 10 This has contributed to the continuous exposure of poultry microorganisms to antimicrobials and, thus, the development of AMR. 11 , 12 Escherichia coli ( E. coli ) are among the commensal or pathogenic microorganisms isolated from poultry that have become resistant to common antibiotics used in human and animal health. 13–16 E. coli causes infections such as urinary tract infections, bloodstream infections, sepsis and meningitis.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 This has contributed to the continuous exposure of poultry microorganisms to antimicrobials and, thus, the development of AMR. 11 , 12 Escherichia coli ( E. coli ) are among the commensal or pathogenic microorganisms isolated from poultry that have become resistant to common antibiotics used in human and animal health. 13–16 E. coli causes infections such as urinary tract infections, bloodstream infections, sepsis and meningitis.…”
Section: Introductionmentioning
confidence: 99%
“… 94 , 104–108 Consequently, there is evidence of antimicrobial-resistant pathogens across the human and animal sectors. 37 , 38 , 41 , 99 , 109–115 A study by Masich et al 116 revealed that about 67% of antimicrobials were inappropriately prescribed to non-critically ill adult patients admitted to the University Teaching Hospital in Lusaka, Zambia. Intriguingly, the Zambian government has put in measures to promote the appropriate use of antibiotics by developing and implementing the National Action Plan (NAP) on AMR.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in antibiotic resistance among Enterococcus species, particularly E. faecalis, underscores the urgent need for the development of new anti-infective therapies [6][7][8]. The surge in antibiotic-resistant E. faecalis strains has increased the urgency for innovative therapeutic approaches, prompting keen interest in phage-based interventions [9][10][11]. This burgeoning interest stems from the demonstrated efficacy of phage therapy (PT) in exerting lytic activity against diverse antibiotic-resistant E. faecalis isolates [12][13][14], thus providing a promising alternative treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…The surge in antibiotic-resistant E . faecalis strains has increased the urgency for innovative therapeutic approaches, prompting keen interest in phage-based interventions [ 9 11 ]. This burgeoning interest stems from the demonstrated efficacy of phage therapy (PT) in exerting lytic activity against diverse antibiotic-resistant E .…”
Section: Introductionmentioning
confidence: 99%